Investigation of fenugreek seeds aqueous extract for prevention of ovarian hyperstimulation syndrome in the rat animal model. - Allow, Ahmed Kaid Naji (2018)
This project was aimed to explore the potential effects of fenugreek seeds aqueous extract (FSAE) on prevention of ovarian hyperstimulation syndrome (OHSS) as will as to find the toxic dose of FSAE in rat model. For SFAE vs OHSS, thirty-four immature, female Sprague Dawley rats, at the age of 18 days post-natal (PN) with body weight around 40 grams were randomly divided into negative control (-C), positive control (+C), and treated (T) groups. The T group rats were treated with FSAE at dose 1500mg/kg body weight/day for thirteen days. The OHSS was induced in both (+C) and (T) groups by using Pregnant Mare’s Serum Gonadotropin (PMSG) and human Chorionic Gonadotropin (hCG). From day 8 to11 (PN 25-28), rats of +C and T were injected subcutaneously (SC) with (50 IU/day) of PSMG. On day 12 (PN 29) rats were injected with 25 IU of hCG. On Day 14 (PN 31) rats were injected with 0.2 ml of 5mM Evan’s Blue dye (EBD) into the femoral vein under anaesthesia. After 30 minutes, the rats were decapitated. The effect of FSAE was evaluated by measuring the VP, VEGF, oestradiol (E2), along with relative ovarian weight and ovarian histological study. For FSAE-toxicity project 12 mice were divided into 4 groups (3 rats/each) and administrated FSAE orally dose of 3, 6 and 9 gm single dose. Liver and kidney tissues and their function tests were investigated. Results of the first part showed that the FSAE decreases VP of OHSS treated group significantly (p-value<0.05). There was a significant increase in relative ovarian weight in treated group groups. FSAE has no significant effect on primary and secondary ovarian follicles and corpora lutea follicles. Graafian follicles is higher in treated group. Atretic follicles were increased significantly in treated group. FSAE reduced significantly serum E2 level in treated group. While no change in serum VEGF was observed. Results of the second part showed FSAE administered doses showed liver histopathological changes in the form of mild portal inflammation, mild mononuclear cell infiltration in hepatic parenchyma, in addition to mild bile stasis induced only in mice received 9g/kg of FSA, but no steatosis induced in all treated mice groups. Kidneys function tests and tissue were without any changes. Concluding that the FSAE may has the ability to prevent OHSS by decreasing the VP and serum E2, and by increasing atretic follicles. FSA showed minimum lethal oral dose of 9g/kg body weight, FSAE administered doses, does not produce any significant acute toxicity as reflected by the various investigated parameters apart of mild liver histopathological inflammatory changes which reflect mild liver injury induced by the all FSA tested doses.